2019
DOI: 10.1088/1757-899x/584/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Swelling Control of Expansive Soils Using Cement Dust

Abstract: Expansive soils exist in many regions over the world including Iraq. Expansive or swelling soil contains minerals that are capable to absorb water easily causing an increase in its volume. In this research, an expansive soil that exists in some locations in the province of Karbala in Iraq was used. Limited data is available to investigate the effect of cement dust on engineering properties of expansive soils. For this purpose, samples have been prepared by mixing the expansive soil with different percentages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This made it possible to labor longer hours all year round as opposed to just during the dry seasons. This result is consistent with research published in 2019 by Almurshedi et al (2019), Rashed et al (2019).…”
Section: Influence Of Cement Kiln Dust On Atterberg Limitsupporting
confidence: 94%
“…This made it possible to labor longer hours all year round as opposed to just during the dry seasons. This result is consistent with research published in 2019 by Almurshedi et al (2019), Rashed et al (2019).…”
Section: Influence Of Cement Kiln Dust On Atterberg Limitsupporting
confidence: 94%
“…Expansive soil samples from southwestern Baghdad have been prepared and blended with different contents of cement dust, (4 to 20)%, by Almurshedi [29]. This modifier considerable observation method to improve geotechnical properties of this soil such as decreasing the consistency limits, (L.L, P.L., P.I), increasing the maximum dry density corresponding to lower optimum water content, decreasing the swelling pressure and swelling potential.…”
Section: Types Of Sustainable Materials According To Their Sources 1-mentioning
confidence: 99%
“…Many studies concluded that adding cement dust on local expensive soil was able to enhance their properties such as decreasing the consistency limits, increasing the MDD corresponding to lower OMC, and decreasing the swelling pressure and swelling potential [7,8,15]. Moreover, Parsons et al [15] reported that using Cement Kiln Dust (CKD) improved the strength of soil with 100-200% and enhanced the soil durability.…”
Section: Cement Dust As a Fillermentioning
confidence: 99%
“…In addition, Adam et al [5] reported that adding lime to the subgrade decreased the required thickness of the pavement structure by about 50-60%. Moreover, adding lime significantly reduces the swelling potential (SP), liquid limit (LL), plasticity index (PI), and maximum dry density (MDD) of the subgrade soil, and increases the optimum moisture content (OMC), shrinkage limit (SL), and material strength [6][7][8].…”
Section: Introductionmentioning
confidence: 99%